Application of therapeutic group therapy and thought stopping for elementary school students - Usraleli Usraleli; Husnan Husnan; Syafrisar Meri Agritubella (Community Empowerment, 2022)
The behavior of school-age children has changed during the pandemic. The implementation of face-to-face learning after the pandemic requires extra adaptation where children have to orient and interact with classmates who were previously online for 2 years. Some of the difficulties faced include pessimistic children, dependence on friends, being alone, disturbing friends and not completing tasks well. This leads to fear, negative thoughts, and an inability to adapt to classmates. Therapeutic Group Therapy (TGT) and Thought Stopping (TS) aim to stimulate cognitive, affective, and psychomotor as well as eliminate negative thoughts and turn them into positive thoughts. This activity was attended by 33 students in grade 3 of SDN 176 Pekanbaru. TKT was conducted in 7 sessions and TS was carried out using a workbook for 3 sessions. The results of this community service activity showed that there was an increase in the ability of children to accept learning and be able to change negative thoughts into positive thoughts.